A case of obstructive jaundice due to early carcinoma of the cystic duct protruding into the common bile duct. (2018) - Sakuraoka, Yuhki; Suzuki, Takashi; Tanaka, Genki; Shimizu, Takayuki; Shiraki, Takayuki; Kyongha, Park; Mori, Shozo; Iso, Yukihiro; Kato, Masato; Aoki, Taku; Kubota, Keiichi; Yamagishi, Hidetsugu
Highlights: An extremely rare early cystic duct carcinoma. The protruding part was the cause of jaundice. There is a significant interesting macro findings in the removed sample. The only small part of the invasive part which reach fibro-muscular layer is revealed by the pathological findings. Abstract: Introduction: Cystic duct carcinoma is a rare disease, and only 33 cases reported worldwide have completely fulfilled the criteria first established by Farrar in 1951. Here we describe an extremely rare case of early cystic duct carcinoma that fulfilled the Farrar criteria, the papillary tumour protruding into the common bile duct, leading to obstructive jaundice. Case presentation: A 76-year-old man visited a clinic with icteric conjunctivae, and was referred to our hospital for investigation of suspected obstructive jaundice. He was initially diagnosed as having a distal bile duct carcinoma on the basis of ultrasonography (US), endoscopic retrograde cholangiopancreatography (ERCP), and magnetic resonance cholangiography (MRC), and underwent pancreatoduodenectomy with regional lymphadenectomy. Macroscopic examination showed that the stalk of the papillary tumour originated from the cystic duct, and that the protruding lesion was 50 mm in size. Histopathological examination revealed the tumour to be a papillary adenocarcinoma confined within the fibromuscular layer, with no evidence of lymph node metastasis. Therefore, the final diagnosis was early cystic duct carcinoma. Conclusion: To our knowledge, this is the first case report of obstructive jaundice due to early carcinoma of the cystic duct protruding into the bile duct, with characteristics fulfilling the Farrar criteria.